Lottie Paris lives here - Johnson, Angela, 1961-; Fischer, Scott M. (New York : Simon & Schuster Books for Young Readers, 2011)
Relates a day in the life of a little girl who lives with her Papa Pete in a house across from a park.
Kirkus Review
Publisher's Weekly
School Library Journal
Kirkus Review, July 2011
Publisher's Weekly, June 2011
School Library Journal, August 2011
Keywords: Day -- Juvenile fiction; Dwellings -- Juvenile fiction; Parks -- Juvenile fiction; Day -- Fiction; Dwellings -- Fiction; Parks -- Fiction; Day -- Fiction; Houses -- Fiction; Parks -- Fiction; Picture books for children